Dallo scavo all’esperienza immersiva: Il progetto Metateca nell’area archeologica di Aquinum - Ceraudo, Giuseppe; Murro, Giovanni Battista; Malakuczi, Viktor; Monastero, Gabriele (Archeomatica, 2018)
The urban area and territory of Aquinum, roman city situated along the route of via Latina were investigated by means of aero-topographical studies, geophysical prospecting and archaeological field survey. The work has been organized according to the great archaeological potentialities and the promising perspectives of research offered by the site. Casale Pascale, a rural dwelling owned by the municipality of Castrocielo, was used to create a new "musealization”: an innovative zoom on the archaeological site, based on augmented reality and of Kinect technology, in order to make intelligible to a wider audience as possible the structural evidence and the significant materials from the excavation.